1997
DOI: 10.1074/jbc.272.27.16896
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Relationship between the Calmodulin-binding, Actin-binding, and Actomyosin-ATPase Inhibitory Domains on the C Terminus of Smooth Muscle Caldesmon

Abstract: Multiple functional domains responsible for calmodulin (CaM) binding and actin-binding/actomyosin ATPase inhibition are present in the region between residues 598 -756 of the chicken gizzard smooth muscle caldesmon (CaD) molecule. To precisely localize these functional domains and to further elucidate the structural basis of these domains, we analyzed a series of purified mutants of chicken gizzard smooth muscle CaD generated by internal deletions of amino acid sequences and expression in a baculovirus express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…In the 'flip-flop' model (Sobue et al, 1983), Ca 2+ -CaM competes with actin for the binding sites on CaD and therefore reverses the inhibitory effects of CaD on actomyosin ATPase by dissociating it from actin filaments. In favor of this model, the Ca 2+ -CaM binding domain has been shown to be juxtaposed to the actin-binding domain (Fraser et al, 1997;Huber et al, 1998a;Wang et al, 1997). By contrast, the 'four state' model proposes that Ca 2+ -CaM can reverse the inhibitory effects of CaD by two means: either by dissociating CaD from the actin filaments or by forming an uninhibited ternary complex of Ca 2+ -CaM-CaDactin-tropomyosin.…”
Section: Discussionmentioning
confidence: 93%
“…In the 'flip-flop' model (Sobue et al, 1983), Ca 2+ -CaM competes with actin for the binding sites on CaD and therefore reverses the inhibitory effects of CaD on actomyosin ATPase by dissociating it from actin filaments. In favor of this model, the Ca 2+ -CaM binding domain has been shown to be juxtaposed to the actin-binding domain (Fraser et al, 1997;Huber et al, 1998a;Wang et al, 1997). By contrast, the 'four state' model proposes that Ca 2+ -CaM can reverse the inhibitory effects of CaD by two means: either by dissociating CaD from the actin filaments or by forming an uninhibited ternary complex of Ca 2+ -CaM-CaDactin-tropomyosin.…”
Section: Discussionmentioning
confidence: 93%
“…Domain analysis of CaD and CaD fragments produced from limited proteolysis, chemical cleavage, and expression systems has led to the precise localization of various functional domains within the CaD molecule (33)(34)(35)(36)(37)(38)(39). For example, the myosinbinding site was first localized to the amino-terminal region of CaD (42,43) and was recently mapped to the sequence between residues 24 and 53 (33).…”
Section: Resultsmentioning
confidence: 99%
“…As we were unable to achieve total knockdown of caldesmon using any of the siRNAs, it is not clear to what extent the structure of stress fibres would be affected in (Velaz et al, 1990;Bogatcheva et al, 1993;Huber et al, 1995) and a tropomyosin-binding site (black) (Smith et al, 1987;. The C-terminal fragment of lcaldesmon (Cad39; amino acids 236-532) contains two tropomyosin-binding sites, two actin-interacting regions (diamonds) (Wang et al, 1997b;Marston et al, 1998), and the two Ca 2+ /calmodulin binding sites A and B, as indicated (dark-grey boxes) Wang et al, 1996). Both Ca 2+ /calmodulin-binding sites contain a key tryptophan residue (W454 and W487) that is essential for this interaction (Graether et al, 1997); replacement of these tryptophan residues with alanine (W454A and W487A) generates an l-caldesmon mutant that is unable to interact with Ca 2+ /calmodulin (CadCamAB).…”
Section: Effects Of Expression Of Egfp-caldesmon On Pdbuinduced Podosmentioning
confidence: 99%
“…We generated an EGFP-caldesmon construct (CadCamAB), in which the two tryptophan residues, W454 and W487, known to be essential for calmodulin-binding were mutated to Ala. The W454A and W487A mutations have been shown to abolish interaction between caldesmon and calmodulin, but have little effect on binding of caldesmon to actin (Graether et al, 1997;Wang et al, 1997b;Li et al, 2004). Depending on the expression level, CadCamAB caused various degrees of stress fibre disassembly.…”
Section: Intact Calmodulin-binding Sites Are Required For Targeting Cmentioning
confidence: 99%